Evaluation of the Effect of Hydroethanolic Root Extract and Solvent Fractions of Cyphostemma adenocaule (Steud. ex A. Rich) Descoings ex Wild & Drummond on Cell-Mediated Immune Response and Blood Cell Count in Mice. (10th February 2021) - Abebe, Dehnnet; Periasamy, Gomathi; Karim, Aman; Bitew, Helen
Abstract : Introduction . Cyphostemma adenocaule (Steud. ex A. Rich) Descoings ex wild & Drummond (Vitaceae) has been used in traditional medicine for the management of various immunological and hematological disorders in different areas of Ethiopia and the rest of the world. In Ethiopia, the plant is used for the management of enlarged spleen, rabies virus, helminthic infection, snake bite, and various types of tumors. Objective . To evaluate the effect of hydroethanolic root extract and solvent fractions of Cyphostemma adenocaule on cell-mediated immunity (delayed-type hypersensitivity), organ index (spleen and liver), and blood cell count in Swiss albino mice. Materials and Methods . Acute oral toxicity test was conducted using nulliparous and nonpregnant Swiss albino mice following OECD 425 limit test method. Delayed-type hypersensitivity model was used to evaluate the effect on cell-mediated immunity. The experimental animals were divided into twelve groups which were sensitized and challenged with sheep red blood cells on day 0 and day 7, respectively. Levamisole 50 mg/kg was used as stimulant control, whereas cyclophosphamide 30 mg/kg was used as suppressant control. Hydroethanolic root extract (100 mg/kg, 200 mg/kg, and 400 mg/kg), aqueous fraction (100 mg/kg, 200 mg/kg, and 400 mg/kg), and n- butanol fraction (100 mg/kg, 200 mg/kg, and 400 mg/kg) were administered for seven days. The paw volume was measured using a digital plethysmometer before challenge and 24 hours after challenge. Blood was collected, and organs (spleen and liver) were isolated from each challenged mouse to determine blood cell count and organ index, respectively. Results . No mortality and noticeable behavioral changes were observed among all mice receiving hydroethanolic root extract and solvent fractions at a dose of 2000 mg/kg. Hydroethanolic root extract and solvent fractions of Cyphostemma adenocaule showed enhancement of delayed-type hypersensitivity, organ index, and blood cell count. Hydroethanolic root extract at a dose of 400 mg/kg showed the highest and statistically significant stimulation of delayed-type hypersensitivity (0.123 ± 0.010) and blood cell count compared to the vehicle. Conclusion . Hydroethanolic root extract and solvent fractions of Cyphostemma adenocaule showed a stimulatory effect on cell-mediated immunity and hematopoiesis.